Radulphus Brito (1290s) on the Syllogism : A Pragmatic Account - Mora-Márquez, Ana María ; 0000-0002-9091-4863 (History and Philosophy of Logic, 2025)
General studies of medieval logic tend to neglect the context in which medieval logic developed and the needs to which such a development responded. Accordingly, they normally neglect the non-formal elements they encounter instead of integrating them as elements that meet the specific needs of the medieval intellectual endeavour and that are, then, part and parcel of medieval interpretations of Aristotelian logic. The result is, at best, a partial picture of medieval logic, with a focus on the formal that in some periods and key authors is unwarranted. In this study, I present the account of the syllogism of a crucial figure of thirteenth-century Aristotelianism, Radulphus Brito. My main aim is to show that Brito puts forth a pragmatic account of the syllogism, which includes pragmatic necessary conditions, such as institutional context, background knowledge and intention of the arguers, functional both at the propositional and the consequential levels. I aim, thus, to provide some nuance to our general picture of medieval logic with Brito’s pragmatic account of the syllogism.
Keywords: Aristotelian logic; dialectic; Medieval logic; Radulphus Brito; syllogism